Low Cost Traditional Cassava Starch Factory Solid Waste (Thippi) Composting: A Possible Strategy for Organic Nutrient Management and Economic Security for Tribal Farmers - Chithra, S; Susan John, K; Sreekumar, J (JOURNAL OF ROOT CROPS, 2017)
In Kerala, cassava tubers are mainly used for human consumption whereas in Tamil Nadu, it is for the production of industrial starch and sago. During the extraction of starch from tubers, both small scale and large starch and sago factories are generating on an average about 40-60 tonnes of solid waste (thippi) per annum creating serious environmental pollution. Considering the voluminous quantity of thippi discharged from these industries, we explored the possibility of making some value added organic manures from thippi. Among the various protocols tried, the cheap and traditional way of composting using earthworms gave better result in making it in to a nutrient rich organic manure. It had the highest plant nutrient content with low C:N ratio (8:1). The mean N, P, K, Ca, Mg, Fe, Mn, Cu and Zn content in thippi compost was 1.32, 3.82, 0.40, 2.18, 0.96, 1.11, 0.08%, 11.23 and 89.93 ppm respectively which is 3.5, 49,7, 32.5, 8, 185, 100, 2.5 and 12 times respective of nutrients compared to raw thippi. A study on the mineralization pattern of nutrients from thippi compost under pot incubation for a period of one year indicated the maximum release of almost all nutrients during 5-7 th month. Field experiments conducted for two seasons to study the effect of thippi compost as a substitute to commonly used organic manures and fertilizers including secondary and micronutrients revealed thippi compost as an alternative to FYM, green manuring in situ with cowpea, crop residue incorporation, vermicompost and coir pith compost and even fertilizers up to N @ 50 kg ha -1 , MgSO 4 @ 2.5 kg ha -1 and ZnSO 4 @ 2.5 kg ha -1 .